Identification of Fake Indian Currency using an Android App - Lakshmi Prasanna N.; Guntur Likhith
This paper seeks to address the problem of counterfeit Indian currency, which creates financial risks and damages trust. Through the application of machine learning and mobile applications, it provides a trusted solution for authenticating currency, improving financial security, and minimizing fraudulent transactions. The Android application enables users to register, login, and take pictures of currency bills using their phone's camera and the user can even upload image of currency bill from the gallery. A machine learning model which is trained using CNN algorithm is used to scan the image and identify whether the currency is authentic or forged. This quick verification process enables users to fight counterfeit currency. The app, built with Kotlin, ensures a smooth interface for easy access and use. Overall, this Android app offers a potential solution to the pervasive issue of counterfeit currency circulation.